A Survey on Cloud Computing Providers and Applications - Yadav, Sukriti; HV, Rakshith; Nath, K. Badari (International Journal of Computer Sciences and Engineering, 2020)
One of the most dominant technologies of today is cloud computing. This dominance is due to its potential to reduce costs while providing the services that are needed to carry out any business more efficiently and effectively. Cloud computing can be deployed universally in very little time. It offers flexibility as well as agility. This paper reviews the features and models of cloud computing. The different models of cloud are discussed in detail and comparison between them is used to understand the functionality and use of each. This paper also provides a comparison between the major cloud computing service providers. The three main cloud providers Amazon, Google, and Microsoft are compared against various features. This helps to understand the services and benefits of each provider. It also includes an overview of the challenges and limitations faced in the field of cloud computing and also the current scope of its application in various industries.